2019
DOI: 10.1002/da.22906
|View full text |Cite
|
Sign up to set email alerts
|

Hub distribution of the brain functional networks of newborns prenatally exposed to maternal depression and SSRI antidepressants

Abstract: Background: Prenatal maternal depression (PMD) and selective serotonin reuptake inhibitor (SSRI) antidepressants are associated with increased developmental risk in infants. Reports suggest that PMD is associated with hyperconnectivity of the insula and the amygdala, while SSRI exposure is associated with hyperconnectivity of the auditory network in the infant brain. However, associations between functional brain organization and PMD and/or SSRI exposure are not well understood. Methods:We examined the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 81 publications
(154 reference statements)
0
14
1
Order By: Relevance
“…As discussed below, gestational SSRI exposure seems to be able to mitigate some of the developmental effects of prenatal stress. It is, however, also able to alter developmental mechanisms and behaviors without counteracting prenatal stress; similar to the human study of Rotem-Kohave et al [145]. That both gestational SSRI exposure and prenatal stress can influence brain development independent of each other is also highlighted in another review focusing specifically on hippocampal plasticity [203].…”
Section: Maternal Ssri Intake Affects Animal Offspring 5-ht Signalingmentioning
confidence: 59%
See 2 more Smart Citations
“…As discussed below, gestational SSRI exposure seems to be able to mitigate some of the developmental effects of prenatal stress. It is, however, also able to alter developmental mechanisms and behaviors without counteracting prenatal stress; similar to the human study of Rotem-Kohave et al [145]. That both gestational SSRI exposure and prenatal stress can influence brain development independent of each other is also highlighted in another review focusing specifically on hippocampal plasticity [203].…”
Section: Maternal Ssri Intake Affects Animal Offspring 5-ht Signalingmentioning
confidence: 59%
“…Hub values of these regions in neonates of SSRI-depressed mothers did not differ from neonates of healthy mothers. These findings may suggest that SSRIs normalize the depression-induced alterations during brain development [145]. Consequently, both maternal depression and prenatal SSRI-exposure might have overlapping underlying mechanisms, which potentially involves the fetal 5-HT system.…”
Section: The Role Of Prenatal Stress In Offspring Brain Development Imentioning
confidence: 86%
See 1 more Smart Citation
“…A critical point to be considered when analyzing the risk of exposure to SSRIs in pregnant women is the psychopathological state of the future mother. Evidence indicates that SSRI treatment in depressed mothers can prevent the modifications in brain’s connectivity produced in newborns that are exposed to unmedicated depressive mothers 211 . In addition, other studies have shown that adverse effects produced by prenatal maternal depression on infant’s problematic temperament can be amplified by a concurrent prenatal traumatic stress 212 .…”
Section: Translational Aspects and Concluding Remarksmentioning
confidence: 99%
“…Several studies report sex differences 30 , with girls showing stronger associations of prenatal exposure to depressive symptoms with functional connectivity in emotion-regulation networks 31 , right amygdala volume 32 , and cortical thickness 33 than boys. Overall, prenatal exposure to SSRIs and maternal depression affect the developing brain in overlapping-but potentially also in distinct brain regions 34 , with a key role for corticolimbic structures such as the prefrontal cortex and the amygdala 25,35,36 .…”
Section: Introductionmentioning
confidence: 99%